From Reading Pictures to Understanding a Story in the Foreign Language - Annett Kaminski (CLELEjournal, 2013)
This paper discusses the impact of pictures on children's understanding of a story during their first encounter with the picturebook The Smartest Giant in Town. The study was conducted with a group of 24 children aged between 8 and 9 years in a German primary school. The recorded classroom discourse revealed that children scanned the pictures for clues and actively constructed meaning from them. Learners demonstrated a solid understanding of the relevant situation, which enabled them to make accurate predictions about the developing narrative on the basis of the illustrations within the picturebook. Data from interviews with three groups of four to five young learners each showed that the children were able to jointly reconstruct the storyline 12 months after their first and only encounter with the picturebook. These findings suggest that one encounter with this picturebook helped to create a meaningful context, within which vocabulary knowledge can be expanded during repeated encounters with the story.